Light Management in 2D Perovskite Toward High-Performance Optoelectronic Applications - Kailian Dong; Tao Jiang; Guoyi Chen; Hongsen Cui; Shuxin Wang; Shun Zhou; Chen Wang; Yi Yang; Fang Yao; Chen Tao; Weijun Ke; Guojia Fang (Nano-Micro Letters)
Highlights The light management strategy is introduced into two-dimensional Dion-Jacobson (2D DJ) perovskite and subsequently elucidated both experimentally and theoretically. The synthesis of surface-patterned BDAPbBr4 microplates with high crystalline quality demonstrates the first reported instance of growing such 2D DJ-type perovskite microplates. The optimized device exhibits excellent photodetection performance under UV region. Moreover, this work represents the successful demonstration of BDAPbBr4 perovskite for UV weak-light communication, imaging, and polarized light detection.